Clinico-Pathological Evaluation of Fever More Than Three Weeks : A Cross Sectional Study in A Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Fever is a common clinical presentation of a number of diseases. A sustained unexplained fever >38.3°C lasting for >3 weeks without an established diagnosis despite intensive diagnostic evaluation is referred to as Fever of Unknown Origin (FUO). Fever more than three week remains a clinical challenge for physicians, as it may be attributed to a wide range of disorders, mainly infections, malignancies, non-infectious inflammatory diseases and miscellaneous diseases. The evaluation of the condition of a patient with fever of unknown origin requires a knowledge of those disorders that produce this syndrome, an awareness of the potential significance of subtle findings in the history and physical examination, and an appreciation of the value in this clinical setting of specific diagnostic procedures. In this report, we review these aspects of fever of unknown origin and outline a diagnostic approach to the persistently febrile patient.Objective: Purpose of this study was to clinico-pathological evaluation of fever more than three weekswith its aetiology and clinical spectrum.Methods: This cross-sectional study was conducted amongst adult males and females patients suffering from the fever of more than three weeks over period of two years at Combined Military Hospital, Chattogram Cantonment from January, 2016 to December, 2017. Sample was selected by purposive sampling technique. Inclusion criteria were H/O fever or body temperature greater than 38.3°C on several occasions, accompanied by more than three weeks of illness and failure to reach a diagnosis after one week of inpatient investigation. Total 72 cases were enrolled according to selection criteria. Routine hematological, biochemical, imaging test were done and mid-stream urine samples were collected from these patients and subjected to culture. Detail demographic data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigation were done meticulously.Results: In this study age of participants at entry was >20years, mean age was 38.04±11.08. Female sex were significant number, sex ratio (F: M) was 1.25:1. Most common clinical presentations were persistent fever and generalized weakness (100.0%), followed by arthralgia/ arthritis (51.3%) anorexia (44.4%) and headache (34.7%). The focused fever of unknown origin diagnostic approach is based on hallmark clinical features characteristic of each disorder. Diagnostic significance of nonspecific clinical findings is enhanced when considered together. Of the infectious diseases that are associated with FUO, tuberculosis (Especially in extrapulmonary sites) was most common cause (eg. 13.8%) and in malignant aetilogy, lymphoma was the major cause (eg. 11.1%) of fever of unknown origin. Abdominal and or Pelvic abscesses (5.6%) Colorectal carcinoma (5.6%) Drug-induced fever (4.1%) UTI (5.6%) SLE (5.6%) Rheumatoid arthritis (9.7%) Dental abscesses (2.7%) and Osteomyelitis (4.1%) were the others common cause of fever of unknown origin.Conclusion: Fever is a common presenting complaint in hospital admitted patients. Most febrile illnesses either resolve before a diagnosis can be made or develop distinguishing characteristics that lead to a clinical dilemma. Fever of Unknown Origin (FUO) is dynamic in its origin and will be an ongoing challenge to the clinician because of shifting disease epidemiology. In this study infection was predominant aetiology for febrile illness. Proper evaluation, rationale use of drugs and health awareness reduced the burden of Fever of unknown origin.Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 6-13